2022
DOI: 10.3390/ijms231710135
|View full text |Cite
|
Sign up to set email alerts
|

Factors and Pathways Modulating Endothelial Cell Senescence in Vascular Aging

Abstract: Aging causes a progressive decline in the structure and function of organs. With advancing age, an accumulation of senescent endothelial cells (ECs) contributes to the risk of developing vascular dysfunction and cardiovascular diseases, including hypertension, diabetes, atherosclerosis, and neurodegeneration. Senescent ECs undergo phenotypic changes that alter the pattern of expressed proteins, as well as their morphologies and functions, and have been linked to vascular impairments, such as aortic stiffness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 149 publications
(164 reference statements)
0
23
0
Order By: Relevance
“…Among these detrimental effects of senescent cell accumulation, complications in the cardiovascular system have been the subject of several recent studies. For example, senescent endothelial cells (ECs) exhibit functional abnormalities, such as decreased expression of endothelial nitric oxide (NO) synthase and increased expression of proinflammatory molecules, contributing to vascular inflammation [34][35][36]. Senescent ECs and other senescent cell types in the cardiovascular system share characteristics with other types of dysfunctional cells.…”
Section: Introductionmentioning
confidence: 99%
“…Among these detrimental effects of senescent cell accumulation, complications in the cardiovascular system have been the subject of several recent studies. For example, senescent endothelial cells (ECs) exhibit functional abnormalities, such as decreased expression of endothelial nitric oxide (NO) synthase and increased expression of proinflammatory molecules, contributing to vascular inflammation [34][35][36]. Senescent ECs and other senescent cell types in the cardiovascular system share characteristics with other types of dysfunctional cells.…”
Section: Introductionmentioning
confidence: 99%
“…High glucose conditions induce premature endothelial cell aging, leading to CBF dysregulation ( Biessels and Despa, 2018 ; Prattichizzo et al, 2018 ; Balasubramanian et al, 2021 ). A recent review ( Hwang et al, 2022 ) extensively summarized the molecular pathways related to endothelial cell aging. Understanding these diabetes-related changes in pathways is of significant importance for improving endothelial dysfunction and CBF dysregulation.…”
Section: Evidence Of Cognitive Decline In Diabetes Patientsmentioning
confidence: 99%
“…Cell senescence is a state of indefinite cell cycle arrest implemented in response to sublethal stresses (Hwang et al, 2022). Current studies have found that dietary restriction (DR) without malnutrition is the most effective way to prevent cell senescence in humans, and in vivo experiments revealed that inhibition of mTORC1 activity in yeast, nematodes, flies, and mammals can lead to a longer lifespan (Vellai et al, 2003;Kapahi et al, 2004;Kaeberlein et al, 2005;Wu et al, 2013;Green et al, 2022).…”
Section: Mtor Signaling Pathway-mediated Cell Senescence In the Patho...mentioning
confidence: 99%